Examination of Complementary Medicine for Treating Urinary Tract Infections Among Pregnant Women and Children - Hudson, Rachel E.; Job, Kathleen M.; Sayre, Casey L.; Krepkova, Lubov V.; Sherwin, Catherine M.; Enioutina, Elena Y. (Frontiers in Pharmacology, 2022)
Urinary tract infections (UTIs) are a significant clinical problem that pregnant women and children commonly experience. Escherichia coli is the primary causative organism, along with several other gram-negative and gram-positive bacteria. Antimicrobial drugs are commonly prescribed to treat UTIs in these patients. Conventional treatment can range from using broad-spectrum antimicrobial drugs for empirical or prophylactic therapy or patient-tailored therapy based on urinary cultures and sensitivity to prospective antibiotics. The ongoing emergence of multi-drug resistant pathogens has raised concerns related to commonly prescribed antimicrobial drugs such as those used routinely to treat UTIs. Consequently, several natural medicines have been explored as potential complementary therapies to improve health outcomes in patients with UTIs. This review discusses the effectiveness of commonly used natural products such as cranberry juice/extracts, ascorbic acid, hyaluronic acid, probiotics, and multi-component formulations intended to treat and prevent UTIs. The combination of natural products with prescribed antimicrobial treatments and use of formulations that contained high amounts of cranberry extracts appear to be most effective in preventing recurrent UTIs (RUTIs). The incorporation of natural products like cranberry, HA, ascorbic acid, probiotics, Canephron® N, and Cystenium II to conventional treatments of acute UTIs or as a prophylactic regimen for treatment RUTIs can benefit both pregnant women and children. Limited information is available on the safety of natural products in these patients' populations. However, based on limited historical information, these remedies appear to be safe and well-tolerated by patients.